2016
DOI: 10.1007/s00296-016-3612-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of febuxostat on insulin resistance and expression of high-sensitivity C-reactive protein in patients with primary gout

Abstract: We aimed to investigate the effects of febuxostat on IR and the expression of high-sensitivity C-reactive protein (hs-CRP) in patients with primary gout. Forty-two cases of primary gout patients without uric acid-lowering therapy were included in this study. After a physical examination, 20 age- and sex-matched patients were included as normal controls. The levels of fasting insulin (INS), fasting blood glucose (FBG), and hs-CRP were determined. IR was assessed using the Homeostasis Model Assessment of Insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
1
16
0
4
Order By: Relevance
“…Reducing (serum and intracellular) uric acid concentrations has been shown to allay features of metabolic syndrome in experimental models. Febuxostat, a xanthine oxidase inhibitor, was associated with reduced insulin resistance in people with gout in a recent observational study [6].…”
mentioning
confidence: 95%
“…Reducing (serum and intracellular) uric acid concentrations has been shown to allay features of metabolic syndrome in experimental models. Febuxostat, a xanthine oxidase inhibitor, was associated with reduced insulin resistance in people with gout in a recent observational study [6].…”
mentioning
confidence: 95%
“…This hypothesis might explain the conflicting results reported in studies investigating the use of urate- lowering treatments in adults with established hypertension or chronic renal disease. Thus, at variance with these data, small pilot studies conducted in children and adolescents showed a reduction in blood pressure [ 63 , 64 ] and improvement in insulin sensitivity [ 99 , 100 ] and CKD [ 101 ] with the use of urate-lowering treatments. We believe further studies are needed before definitive conclusions can be drawn regarding the reversibility of the mechanisms sustaining the relationship between fructose, uric acid and all the metabolic dysregulations.…”
Section: Why Are These Pathogenetic Mechanisms Extraordinarily Impmentioning
confidence: 99%
“…Some studies also displayed an obvious relationship between uric acid and diabetes risk, and hyperuricemia or gout was associated with diabetes risk 5‐7 . In addition, many patients with hyperuricemia or gout have increased insulin resistance (IR) before the onset of diabetes, which is defined as a decline in the sensitivity of target organs or tissues to insulin and could play a critical role in the pathogenesis of diabetes 8,9 …”
Section: Introductionmentioning
confidence: 99%